â€œAre You One of Us?â€ Points of Social Exclusion amongst Youths of Diverse Religious Groups in Indonesia - Wulandari, Roosalina; Poerwandari, E. Kristi (Humaniora: Journal of Indonesia Culture and Society, 2021)
Deriving from basis of the social identity theory and its development, the research aimed to explore the points of exclusion and how individuals and groups perceived themselves as experiencing victimhood of social injustice. The rise of intolerance in Indonesia was alarming and threatened the diversity and inclusivity of the nation. Throughout several political milestones such as gubernatorial and presidential elections, identity had been used as one of the most efficient ways to segregate and discriminate against people belonging to different groups. Applying a qualitative approach, data were mined from two focus group discussions of university student respondents with various religious and ethnic backgrounds representing the majority and minority groups in Indonesia. Groups sessions were strictly differentiated between majority and minority representatives to minimize the risk of potential conflict. The findings suggest that both groupsâ€™ initial perceptions towards members of outgroups are heavily influenced by transferred stereotypes and prejudices from the older generations. While the majority group struggles to counter the prejudices and perceived victimhood through direct exposure, the minority group, on the other hand, takes language into account as a subtle gesture of exclusion.